If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k/7+-23=-16
We move all terms to the left:
k/7+-23-(-16)=0
We add all the numbers together, and all the variables
k/7-7=0
We multiply all the terms by the denominator
k-7*7=0
We add all the numbers together, and all the variables
k-49=0
We move all terms containing k to the left, all other terms to the right
k=49
| –13t+19t−–18=–12 | | 7-4x-8=19 | | –10h−–8h=8 | | 10-6f=-10-10f | | 2r+5(-6-8r)=5r-4r | | -1=7b-5-8b | | P=5m^2+12m+2 | | -9x+8=-8x+6 | | 4(5x−3)=3(2x+1) | | (c/4)+5=6 | | 20+(y-10)= | | 4r-2-4=14 | | 20=1-8x+3 | | z/–4+13=17 | | -4=4+6v-5v | | 2b^2=5b+12 | | -2-33/b=12 | | 4x+5+8x+30=180 | | (6x+8)+(4x+13)+(11x+12)=x | | (6x+8)=(4x+13)+(11x+12)=x | | 12x+5+30=180 | | (100+w)(150+w)=2(100)(150) | | Q+10=n25 | | -2x-9=9+x | | (6x+8)=(4x+13)+(11x+12) | | 93=2g—27 | | (6x+8)=(4x+13)+(11x+12)+x | | -3x^2-36x=300 | | 9(x-2)=7x-5 | | 4z+8=40* | | 3u—-3=15 | | -8=5v+3+6v |